The Effects of FGF8 and Shh on Expression of Dopaminergic Markers from Human Amniotic Epithelial Cells - Ahmadian A; Peirovi H; Niknejad H; Jorjani M (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2011)
Background and Objectives: Recently, interest has increased in the potential employment of embryonic stem cells for the treatment of Parkinson's disease, which has been considered as an alternative therapeutic strategy. Due to their pluripotent differentiation potential, the finding that they do not induce carcinoma and the fact that they do not raise the ethical concerns connected with human embryonic stem cells, human amniotic epithelial cells are considered to be a very promising cell source. The aim of this study was to investigate the effects of FGF8 and Shh on the expression of dopaminergic markers from human amniotic epithelial cells.Methods: In this study, we examined the differentiation of dopaminergic neurons in vitro from AECs using the expression of several markers including TH, DAT and DβH. For dopaminergic differentiation, sonic hedgehog (Shh) and FGF8 were added to cultures and the cultures were allowed to differentiate for 21 days. Analysis of AECs derived dopaminergic neurons was performed at the TH, DAT, β-tubulin III and DβH expression levels by immunocitochemistry. The significance of the data was tested by Student's t-test (between two groups) and one-way analysis of variance (ANOVA) followed by Tukey post-test. (p<0/01, p<0/05)Results: Combination of Shh and FGF8 showed the higher level of TH in comparison to control group or these factors alone. Moreover, Shh is more effective than FGF8 on DAT expression in comparison to expression of DβH.Conclusion: These results show the capability of AECs to express dopaminergic neural markers and this ability is affected by Shh and FGF8.